2017
DOI: 10.14687/jhs.v14i1.4354
|View full text |Cite
|
Sign up to set email alerts
|

The effect of education on gender perception and gender role attitudes: An experimental study<p>Toplumsal cinsiyet algısı ve toplumsal cinsiyet rollerine eğitimin etkisi: Deneysel bir çalışma

Abstract: Sex has been the most important criteria when categorizing and differentiating individuals. While the concept of sex is used to describe the biological side of being a man or woman, the concept of gender refers to the expectations and meanings formed by the society and culture. In this respect, passive roles are thought suitable for women in the social life while men have more active roles. Socialization agents, such as family, media, peer groups and education are playing an active role in transferring the cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 3 publications
0
2
2
Order By: Relevance
“…In contrast to the results of this study, it was expressed in the study of Özpulat and Özvarış (2019) conducted with the students (n=360) from the Department of Nursing and Department of Nutrition and Dietetics that there was no statistically significant difference between the class variable and gender perception score [16]. It was emphasized that the "Instructional Training for Gender Equality and Fighting with Violence Against Women" given (n=28) in the study with pretest and posttest design conducted by Uzun et al (2017) positively affected the participants' gender perceptions and attitudes towards gender roles [25]. It was determined that those who had gender courses in their curricula had higher gender perceptions than those who did not [6].…”
Section: Discussioncontrasting
confidence: 68%
“…In contrast to the results of this study, it was expressed in the study of Özpulat and Özvarış (2019) conducted with the students (n=360) from the Department of Nursing and Department of Nutrition and Dietetics that there was no statistically significant difference between the class variable and gender perception score [16]. It was emphasized that the "Instructional Training for Gender Equality and Fighting with Violence Against Women" given (n=28) in the study with pretest and posttest design conducted by Uzun et al (2017) positively affected the participants' gender perceptions and attitudes towards gender roles [25]. It was determined that those who had gender courses in their curricula had higher gender perceptions than those who did not [6].…”
Section: Discussioncontrasting
confidence: 68%
“…Raising these scores with education is more difficult in this case, so education may not affect gender role attitudes and gender perception. When studies showing the benefits of education are examined from the literature, it is seen that the pretest scores of the students are lower than those in this study (for perception, Uzun et al, 2017;for attitude, Egelioğlu Cetişli et al, 2017;Koç et al, 2021). In this study, the students' high scores in the pretest on the gender-related scales may be because they are university students (Vefikuluç et al, 2007;Yılmaz et al, 2009;Kahraman et al, 2014), come from regions with a relatively higher socioeconomic status (Kul Uçtu and Karahan, 2016), and there are more students from the nuclear family rather than the traditional extended family (Kul Uçtu and Karahan, 2016).…”
Section: Discussioncontrasting
confidence: 49%
“…Although it was found in this study that education did not affect gender roles attitudes and gender perception, it is essential to provide education on gender to raise awareness about gender equality and develop egalitarian gender roles (Egelioğlu Cetiflli et al, 2017;Uzun et al, 2017). For instance, one study found that students' attitudes toward gender roles were influenced by the gender equality course, with students' attitudes becoming more egalitarian after the course (Egelioğlu et al, 2017).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Also, it was determined that females were more egalitarian in gender roles than males and they support dating violence less than males. In the literature, there are studies that shows male students have more traditional attitudes and perspectives towards gender roles than female students (Uçar et al, 2017;Yılmaz et al, 2009;Sis Çelik et al, 2013;Dinç and Çalışkan, 2016;Reyes et al, 2016;Ünal et al, 2017;Uzun et al, 2017;You & Shin, 2020) and studies that shows level of acceptance of violence by female students are lower than males (Erdem & Şahin, 2017;Uçar et al, 2017;Karabacak & Kodan, Çetinkaya, 2015;Anderson et al, 2011). It can be explained because of the culture and family structure.…”
Section: Extended Abstractmentioning
confidence: 99%